Comparative analysis of the legal regulation of recognition and enforcement of foreign judgments in Republic of Kazakhstan and Russian Federation - Starozhilova, N.P. (KSU publ, 2015)
The author explores the legal regulation of the recognition and enforcement of foreign judgments in the Republicm of Kazakhstan and the Russian Federation. The article examines various types of jurisdiction in international civil procedure, the proceedings for submission and consideration of applications for enforcement of foreign judgments in courts of the states.
Keywords: international civil procedure; systems of jurisdiction determination; immunity of a foreign state; exequatur